The Relationship between Body Mass Index and Mental Health Among Iraq and Afghanistan Veterans - Maguen, Shira (Springer-Verlag, 2013)
BACKGROUND: Obesity is a growing public health concern and is becoming an epidemic among veterans in the post-deployment period. OBJECTIVE: To explore the relationship between body mass index (BMI) and posttraumatic stress disorder (PTSD) in a large cohort of Iraq and Afghanistan veterans, and to evaluate trajectories of change in BMI over 3 years. DESIGN: Retrospective, longitudinal cohort analysis of veterans’ health records PARTICIPANTS: A total of 496,722 veterans (59,790 female and 436,932 male veterans) whose height and weight were recorded at the Department of Veterans Affairs (VA) healthcare system at least once after the end of their last deployment and whose first post-deployment outpatient encounter at the VA was at least 1 year prior to the end of the study period (December 31, 2011). MAIN MEASURES: BMI, mental health diagnoses. KEY RESULTS: Seventy-five percent of Iraq and Afghanistan veterans were either overweight or obese at baseline. Four trajectories were observed: “stable overweight” represented the largest class; followed by “stable obese;” “overweight/obese gaining;” and “obese losing.” During the 3-year ascertainment period, those with PTSD and depression in particular were at the greatest risk of being either obese without weight loss or overweight or obese and continuing to gain weight. Adjustment for demographics and antipsychotic medication attenuated the relationship between BMI and certain mental health diagnoses. Although BMI trajectories were similar in men and women, some gender differences were observed. For example, the risk of being in the persistently obese class in men was highest for those with PTSD, whereas for women, the risk was highest among those with depression. CONCLUSIONS: The growing number of overweight or obese returning veterans is a concerning problem for clinicians who work with these patients. Successful intervention to reduce the prevalence of obesity will require integrated efforts from primary care and mental health to treat underlying mental health causes and assist with engagement in weight loss programs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-013-2374-8) contains supplementary material, which is available to authorized users.